Impacto da política nacional de medicamentos (PNM) no acesso a medicamentos gratuitos - Crispim, Rute Irene Cláudio (2008)
This work aims at the investigation of access to medicines free for users of SUS through the National Drug Policy. The database was used to PENAD98/03. In this research used is a model that conceitua access according to the individual use of the public health service, and receiving the medicine free taking into account the characteristics that lead to use those services. Through Logist model by the method of maximum likelihood has been unable to verify that access to free medicines rose between 6% and 9 percentage points five years after the promulgation of the PNM. The descriptive review with respect to the receipt of free product per lane-income, shows that even among users of SUS, those with higher incomes have a lower probability of receiving free medication. And for the carriers of chronic diseases such as diabetes and hypertension, are more likely to receive free medicine. These results show some effectiveness of the public service to reach those who are really in need.